Analyzing of Consumer Price Index Influence on Inflation in Cilegon City for the Years 2023-2024 - Atira Keisha Belva Armanda Fadhila; Patricia Pingkan Kumenap; Stella Caroline Roma Ito; Zilda Ainun Tazkia; Isnaini Mahuda; Yanyan Dwiyanti (Faculty of Engineering, Univesitas Sultan Ageng Tirtayasa, 2025)
The Consumer Price Index (CPI) in Cilegon City is an important barometer for measuring the inflation rate in the region. Inflation itself is an economic phenomenon that reflects the general increase in the prices of goods and services over a certain period. As a crucial indicator, inflation affects purchasing power, the cost of living, and overall economic stability. Therefore, monitoring the CPI in Cilegon is highly relevant for understanding local economic dynamics and formulating appropriate policies. This study aims to determine whether the Consumer Price Index impacts inflation in Cilegon City. The study results indicate that the CPI has a significant and negative influence on inflation in Cilegon City for the years 2023-2024. Furthermore, the coefficient of determination shows that approximately 57.76% of the variability in the CPI in Cilegon can be explained by the inflation rate, while the remaining 42.24% comes from variables not accounted for in the model.